PERSEBARAN LOGAM Pb DALAM AIR TANAH DI SEKITAR AREA PENIMBUNAN ABU BATU BARA PADA LAHAN BEKAS TAMBANG KOTA SAWAHLUNTO - Harian, Dedi; Indah, Shinta; Nur, Ansiha (Universitas Pendidikan Ganesha, 2025)
Fly ash and bottom ash (FABA) in Sawahlunto City are backfilling materials for former mining areas. The FABA dumping is estimated to hurt groundwater. This study aims to analyze the concentration of Pb metal in groundwater and its distribution using response surface methodology. This study is a quantitative experimental field research using Response Surface Methodology (RSM). The research subjects involved were groundwater samples from four different points around the fly ash and bottom ash (FABA) dumping location in Sawahlunto City. The data collection method was carried out by taking groundwater samples three times consecutively with a three-week interval, following the procedures of SNI 6989.58: 2008 and SNI 6989-84: 2019. Data analysis methods included ANOVA and RSM tests in the SAS platform. The research findings showed that the groundwater at the study location did not meet drinking water quality with a Pb concentration of 0.144 mg/L exceeding the quality standard (0.01 mg/L). The accumulation of FABA in former mining areas pollutes groundwater with Pb parameters. The distribution pattern of Pb decreases with increasing distance and increases with increasing time. Therefore, the government needs to re-evaluate the implementation of FABA utilization as a filling material for former mining areas. The implications of this study indicate the need to re-evaluate the practice of FABA disposal in mine pits, as improper waste disposal will negatively impact groundwater quality.